Peningkatan Keterampilan Membaca Dan Menulis Arab Pegon Santri TPQ Al-Hikmah Sekuning Besowo Kepung Kediri - Siti Marfuah; Siti Nurjanah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
In order to preserve the tradition of writing using Pegon Arabic which is now rarely done, it is necessary to take action, one of which is through the learning of Pegon Arabic writing. Unfortunately, now Pegon's Arabic literacy teaching has weakened. This is evidenced by the facts that the author encountered regarding Pegon's Arabic literacy teaching. The partner of community service activities is TPQ Al-Hikmah, a hamlet of besowo village. Actually, the learning process at TPQ is not only focused on teaching to read the Qur'an but also learning about literacy using the Pegon Arabic script. But in the understanding of the pegon script is still very minimal. with the presence of this pegon arabic material. The research approach used in this study is the PAR ( Participatory Action Research) method. With the researcher program, namely "Improving Arabic Reading and Writing Skills Pegon Santri TPQ Al-Hikmah" on July 26 in Sekuning Hamlet, Besowo Village, Kepung District, Kediri Regency, more or less added changes to the students of volume 4 who have received material about Arabic pegon, students have been able to distinguish which letters can be merged and which cannot be combined. We convey this on some of the data we obtained after this program was implemented. Students who previously did not really understand the Arabic letter pegon that can be merged and those who cannot be merged become more familiar with the existence of this Arabic pegon material